Analysis Of Quality Of Service Factors On Patient Satisfaction In Specialist Polyclinics Rsud Kh Daud Arif Kuala Tungkal, Tanjungjabung Barat, Jambi : tangible (bukti fisik), reability (keandalan), responsiveness (daya tanggap), assurance (jaminan), emphaty (empati) - Hilal, Zaimah; Aini, Subang; Rahmawati, Dwi (FAKULTAS KEDOKTERAN DAN ILMU KESEHATAN UNIVERSITAS JAMBI, 2023)
ABSTRACTBackground: Based on data shows that the number of outpatients who got treatment by specialistpolyclinic RSUD KH Daud Arif in January-June 2018 experienced a decreased each month.Meanwhile increased on March. Early survey have done by researcher about patient satisfaction ofhealth service quality at specialist polyclinic RSUD KH Daud Arif over 10 patients who went treatmentto specialist polyclinic RSUD KH Daud Arif, kuala tungkal, that 6 patients said less satisfied with theservices provided and 4 patients said satisfied with the services provided.Method: The purpose of research is analyzing factors of service quality over patient satisfaction atSpecialist Polyclinic RSUD KH Daud Arif in 2018. The type of research is cross sectional. The sampleof research are some patients at Specialist Polyclinic RSUD KH Daud Arif about 99 respondent. Thedata analysis used chi- squere and regresi logistic.Result: The result of research showed that there are significantly related tangible, reability,responsiveness, assurance, and emphaty over service quality at Specialist Polyclinic RSUD KH DaudArif in 2018 with p-value = 0.000, And after multiple logistic test from 3 type obtained that the mostdominant factor influence to hospital service quality that is tangible with exponent value B 420,578 andp-value = 0.000.Keywords: Characteristics of Respondents, Hospital service quality, tangible,reability, responsiveness,assurance, and emphathy